The reform of the “annoying” universal jurisdiction and its consequences - Martínez Guerra, Amparo (EUNOMÍA. Revista en Cultura de la Legalidad, 2014)
The amendment of the universal jurisdiction principle pursuant to the Organic Law of the Judicial Branch 1/2014, 13 March hinders one of the most powerful instruments to fight against impunity for international crimes. The first decisions of the National and Supreme Court on the matter show serious inconsistencies of this new regulation that affect constitutional rights, international treaty obligations, division of powers and access to justice.
Keywords: Universal jurisdiction principle; universal justice; Organic Law of the Public Branch; genocide; crimes against humanity; war crimes; piracy; drug trafficking; access to justice